Stereoselective Ring-Opening (Co)polymerization of β-Butyrolactone and ε-Decalactone Using an Yttrium Bis(phenolate) Catalytic System - Kiriratnikom, Jiraya; Robert, Carine; Guérineau, Vincent; Venditto, Vincenzo; Thomas, Christophe M. (Frontiers in Chemistry, 2019)
An effective route for ring–opening copolymerization of β-butyrolactone (BBL) with ɛ-decalactone (ɛ-DL) is reported. Several di- and triblock copolymers (PDL-b-PHB and PDL-b-PHB-b-PDL, respectively) were successfully synthesized by sequential addition of the monomers using (salan)Y(III) complexes as catalysts. Microstructures of the block copolymers characterized by 13C NMR spectroscopy revealed syndiotactic-enriched poly(3-hydroxybutyrate)s (PHB) blocks. The results from MALDI-ToF mass spectrometry confirmed the presence of the copolymers. Moreover, thermal properties of the block copolymers were also investigated and showed that the microphase separation of PDL-b-PHB copolymers into PHB and PDL rich domains has an impact on the glass transition temperatures of both blocks.